Influence of environmental factors and race on performance and on carcass traits of swine in a progeny test - Costa, Cláudio Nápolis; Fávero, Jerônimo Antonio; Leitão, Geísa Ribeiro (Pesquisa Agropecuaria Brasileira, 2014)
Data from 1372 boars of Landrace (614). Largo White (515) and Duroc (243) breeds on progeny test at the Estação de Avaliação de Suínos (Swine Evaluation Station), in Concórdia, SC, Brazil, were analysed from 1975 to 1981 to evaluate the effects of environmental factors and time trends on performance and carcass traits. The first degree (linear) for lean: fat ratio, carcass weight, loin-eye area and ham weight, carcass length, and food conversion within the Duroc breed, average daily gain, backfat thickness, carcass yield, and food conversion within Landrace and Large White breeds were the best fitting polynominals to year effects. The seasonal effect, hot weather (October-March) minus cold weather (April-September) differences (P < 0.05) in food conversion, carcass length, carcass yield and ham weight were 0.05, -0.58 cm, 0.24% and 0.13 kg. Differences between breeds for backfat thickness and carcass weight were not significant (P > 0.05). The Duroc breed showed the lowest (P < 0.05) carcass length. In general, the Large White breed was better for performance, and the Landrace for carcass traits. The time trends effectively showed no evidence of generation of progress on the traits evaluated, suggesting the adoption of more efficient methods of testing and selection to obtain progress in a shorter time.
Keywords: nongenetic factors; breeding; Duroc; Large white; Landrace; selection